To find the sum of \( p \) and \( q \), where \( p = -59 \) and \( q = -29 \), you follow these steps:
-
Identify the values: You have \( p = -59 \) and \( q = -29 \).
-
Set up the equation: The sum of \( p \) and \( q \) can be expressed as: \[ p + q = -59 + (-29) \]
-
Combine the terms: When you add two negative numbers, you can add their absolute values and keep the negative sign: \[ -59 + (-29) = -59 - 29 \]
-
Perform the addition: Calculate the sum of the absolute values: \[ 59 + 29 = 88 \]
-
Apply the negative sign: Since both numbers are negative, the result remains negative: \[ -59 - 29 = -88 \]
Therefore, the sum of \( p \) and \( q \) is: \[ p + q = -88 \]